2009
DOI: 10.1080/00222340902841206
|View full text |Cite
|
Sign up to set email alerts
|

Phase Separation in Poly(Methyl Methacrylate)-Epoxy Blend

Abstract: Diglycidyl ether of bisphenol A (DGEBA) epoxy resin was modified with high molecular weight poly(methyl methacrylate) (PMMA). Morphological variations of a 2 wt% PMMA-modified epoxy mixture were studied by optical microscopy and scanning electron microscopy (SEM). A PMMA-epoxy blend cured at 100 • C revealed that a secondary phase morphology was observed in both epoxy and PMMA phases from the early stages of the phase separation process. A morphology consisting of a rough striated continuous phase along with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…As reported by previous studies [5][6][7], the polymer blending of epoxy and PMMA required the aid of solvent (CH 2 Cl 2 ) for blending to happen. However, through this method, lots of solvent is needed for the sample preparation steps and is removed before the samples is shaped into its final form.…”
Section: Introductionmentioning
confidence: 76%
“…As reported by previous studies [5][6][7], the polymer blending of epoxy and PMMA required the aid of solvent (CH 2 Cl 2 ) for blending to happen. However, through this method, lots of solvent is needed for the sample preparation steps and is removed before the samples is shaped into its final form.…”
Section: Introductionmentioning
confidence: 76%
“…Many studies have reported on the usage of the immiscible polymer blend in thermoset/thermoplastic to provide a double percolation condition in order to lower the P c . In general, thermoset/thermoplastic blend systems can be prepared using several methods, including, melt blending, high temperature mixing, and solvent deposition . Studies are focused on the dispersion of filler and the optimum filler loading in relation to the electrical conductivity of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the rubber which is in general soluble in the uncured epoxy resin, precipitates out from solution during the curing process, forming a fine and homogeneous dispersion of rubber particles. In order to overcome the drawback of the detrimental effect on the thermal properties due to incorporation of liquid reactive rubbers, thermoplastics have been used to toughen epoxy resins 1,[14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%